Characterization of dry-cured shoulders: Quality traits - Reina R.; Ventanas J.; López P.; García C. (7th International Symposium on the Mediterranean Pig, 2012)
The present study show some of the chemical and compositional characteristics of dry-cured shoulder from Iberian pigs fed with different diets and dry-cured shoulder produced with the rules of "Protected Designation of Origin Teruel ham". The existence of a quality rule makes the meat industries to follow different guidelines, from the selection of the genetic of the animal, food stuff and processing technology. As well, these rules establish different parameters that must be analyzed to avoid a possible fraud to the consumer. Not significant differences were found in the chemical parameters used by the quality standard, as fatty acids profile, in our samples. For this reason we must search other parameters to justify it. For that the use of products with characteristics very similar to the dry-cured ham which process time is shorter than that, like dry-cured shoulder, can help us to obtain good results which can be extrapolated. The aim of this study is to establish which structure and composition parameters of shoulders are more useful as quality indicators studying different dry-cured shoulders batches (white pigs vs Iberian pigs) depending on the genetic background of the animal and the type of feeding system during the final feeding phase.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)